TINGKAT KECEMASAN ATLET BK PORPROV XIV FUTSAL PUTRI KABUPATEN KUNINGAN PADA SAAT LATIHAN, UJI COBA DAN PERTANDINGAN - Tia Setiani (Journal of Physical Education and Sport Science, 2021)
Anxiety Levels of BK PORPROV XIV Women's Futsal Athletes in Kuningan Regency During Training, Trials and Competitions, Department ofHealth Physical Education and Recreation, 2021. This study aims to determine the level of anxiety of female futsal athletes of BK PORPROV XIV Kuningan Regency during practice, trials and matches. This research uses descriptive quantitative research methods. The population and sample in this study were the women's futsal team of BK PORPROV XIV Kuningan Regency, totaling 18 people. The instrument used in this study was a questionnaire. The data analysis technique of this study tested the validity, reliability and statistical tests using SPSS. The results showed that the anxiety level of the women's futsal BK PORPROV XIV athletes in Kuningan Regency during training was in the moderate category of 44.44% (8 people), at the time of the trial the athlete's anxiety level was in the moderate category of 50% (9 people), and during the match the athlete's anxiety level was in the high category of 55.55% (10 people). The conclusion in this study showed that the level of anxiety of the female futsal BK PORPROV XIV athletes in Kuningan Regency during training, trials, and matches increased.